Assessment Of Wood And Alternative Materials For Supplemental Roof Support Construction - Thomas M. Barczak (International Conference on Ground Control in Mining, 1994)
The engineering of a support system is driven largely by economics. The goal is to provide effective support at minimal cost. For this reason, wood has been extensively used as a support material for centuries. The cost of timber for mining applications has risen by more than 50% in the past 5 years and is likely to continue to increase as the supply diminishes and further environmental restrictions are placed on timber harvesting. The increased cost and lack of high strength wood in the Western United States has provided incentives to improve the utilization of wood and to develop alternative support materials. This U.S. Bureau of Mines' (USBM) report discusses the basic engineering requirements for the application of various materials for supplemental roof support construction and provides an overview of support systems that use materials other than wood. A comparison of support performance and cost for various material constructions is made to assist the mine operator in support selection. The scope of materials discussed in the report include: (1) conventional mine timber loaded perpendicular to the grain, (2) parallel to the grain timber loading, (3) steel fiber reinforced and air entrained concrete, (4) steel, (5) granular fill materials, and (6) combinations of these as composite support structures. The range of support systems analyzed include wood and concrete cribs, concrete columns and props, steel beams, friction props, and several novel support concepts.